Numerical simulation and application of argon blowing from tundish cover for bloom continuous casting - Wu, Chenhui; Li, Yang; Liu, Ying-dong; Xie, Xin; Wu, Guo-rong; Zhang, Min (Journal of Mining and Metallurgy, Section B: Metallurgy, 2023)
During the continuous casting process, the residual oxygen in the tundish can be significantly reduced by argon blowing from the tundish cover (ABTC). As a result, the effect of protective casting can be obviously improved, which helps to reduce the reoxidation of molten steel in the tundish. In the present work, numerical models for the ABTC of a six-strand continuous casting machine were established and verified by the measured oxygen mass fraction in the tundish during the ABTC. The results indicate that the best conditions for ABTC are to install the argon pipes on either side of the tundish cover holes, seal the baking holes, and keep the stopper rod holes open. The argon flow rate should be ≥120m3/h during the period of empty tundish and ≥60m3/h during the period of normal casting. Based on the calculation results, industrial testsof ABTC were carried out. The results indicated that the increased nitrogen content in steel(△w[N]) decreased by 21.5% from 8.78×10-6 to 6.89×10-6 , from the end of RH to tundish, and the amount of inclusions except for MnS in bloom (scanned size: 8mm×8mm) decreased by 21.3% from 13.43 to 10.57, and the average size of inclusions decreased by 19.0% from 9.27μm to 7.51μm.